Cavity magnomechanical storage and retrieval of quantum states. (21st April 2021) - Sarma, Bijita; Busch, Thomas; Twamley, Jason
Abstract: We show how a quantum state in a microwave cavity mode can be transferred to and stored in a phononic mode via an intermediate magnon mode in a magnomechanical system. For this we consider a ferrimagnetic yttrium iron garnet (YIG) sphere inserted in a microwave cavity, where the microwave and magnon modes are coupled via a magnetic-dipole interaction and the magnon and phonon modes in the YIG sphere are coupled via magnetostrictive forces. By modulating the cavity and magnon detunings and the driving of the magnon mode in time, a stimulated Raman adiabatic passage-like coherent transfer becomes possible between the cavity mode and the phonon mode. The phononic mode can be used to store the photonic quantum state for long periods as it possesses lower damping than the photonic and magnon modes. Thus our proposed scheme offers a possibility of using magnomechanical systems as quantum memory for photonic quantum information.